An analysis of utility meter data aggregation and tenant privacy to support energy use disclosure in commercial buildings. (15th September 2018) - Livingston, Olga V.; Pulsipher, Trenton C.; Anderson, David M.; Vlachokostas, Alex; Wang, Na
Abstract: A growing number of cities are adopting energy use benchmarking ordinances, which require building owners report their buildings' total energy usage annually. It also requires that utilities supply aggregated building-level monthly energy consumption data. The data aggregation poses privacy concerns, as it is possible to estimate the individual tenant load consumption curve by dividing aggregated energy data by the number of meters. A solution is to quantify and assess the impact of adjusting the utility meter aggregation threshold on tenant privacy and on buildings that are eligible for energy usage reporting. As the threshold increases, fewer buildings are eligible for energy use data disclosure and therefore lessening data value. This study aims to investigate the similarity between individual utility meters and whole-building totals at various aggregation levels. Based on statistical analysis of 715, 000 anonymized, non-residential meter accounts from six utilities across the U.S., we developed the "Meter Aggregation Selection Threshold" as a metric to assess tenant privacy risk. The metric estimates the portion of individual customer energy use patterns that are similar to the aggregated building consumption profile. It allows policy makers to make an informed decision on whether required disclosure regulations compromise business sensitive information and tenant privacy. Highlights: US cities have adopted building energy use benchmarking ordinances. Benchmarking requires the release of whole-building energy use data. Energy use data pose privacy concerns and reveal business sensitive information. We propose a metric to quantify the privacy risk due to energy use data release. The metric can serve as a policy making tool for informed decisions.